Caracterización psicométrica de una versión reducida del cuestionario de ideación suicida SIQ – HS, adaptado al español, en estudiantes de Pasto - Sevillano Aguiño, Fátima Tatiana; Villalobos-Galvis, Fredy Hernán (Universidad y Salud, 2008)
The main objetive of this study was to identify the psychometric properties of the Suicidal Ideation Questionnaire (SIQ-HS) in a young people sample of students of the San Juan de Pasto city. An instrumental-descriptive, study was done with a transversal non-experimental design. It implies the participation of 333 students of 6 high school and 2 universities, from 14 to 25 years old. A 23-items version of the SIQ-HS, was used and a battery of tests to depression, self-esteem, hopelessness, social support, reasons for living, resilience and suicidal thoughts. It was developed a exploratory factor analysis by principal components. A unique factor structure, which explains the 58,2% of the total variance of the test was found. That structure was maintained across the sub-groups of men, women, and high school and university students. In the reliability analysis was found a Cronbach’s Alpha coefficient of 0,966, which implies a high internal consistence. In the same way, was found significant correlations with suicidal is ideation theoretically related variables. Additionally, it was found that women have higher scores than men. It was concluded that SIQ-HS-23 is an instrument with adequate reliability and validity levels, which makes possible its use in similar student populations.